Management of corporate identity and extra role behavior from the perspective of teachers and administrative workers: Pedro Ruíz Gallo University case - Echeverría Jara, José Foción (2018)
The purpose of the present investigation was to analyze the management of the corporate Identity of the National Uni-versity Pedro Ruiz Gallo; As an initial step, we analyzed the perceptions that teachers and administrative workers have about the management of corporate identity in the university and its effects on attitudes and behaviors. The tar-get population was all teachers and administrative appointed, year 2015. The study was conducted on a simple ran-dom sample of 149 teachers and 161 administrative workers, with a confidence level of 95% selected in a stratified manner. Two questionnaires were applied; one to the teachers and another to the administrative staff, both instru-ments to gather information of the management of the corporate identity in the university. The validity of the instru-ments was tested, corroborating that the adequacy measure of KMO is greater than 0.5; the communalities exceed the established value of 0.4; Barltlett's sphericity test in its degree of significance is less than 0.05. The verification of the reliability of the instruments was carried out using the Cronbach's Alpha method, considering the typified elements, reporting 91.1% and 93.2%, respectively, for the global instrument of the teachers and administrators. The methodol-ogy used was descriptive statistics, frequencies and Pearson's correlation coefficient.